Areas of the international management of the Ecuadorian State in Human Rights - Valencia, José (2016)
This article analyses five different ways through which Human Rights-related International law bring about obligations for any State which has subscribed international instruments and, more specifically, for Ecuador. There is also an effort to identify the main subjects that the Ecuadorian State should have to take into account so as to design an international working plan on human rights.